Asymptotic behavior of solutions of sum-difference equations - Adiguzel, H.; Can, E. (Bulletin of the Karaganda University. Mathematics Series, 2023)
In this study, we present an investigation of the asymptotic behavior of solutions of sum-difference equations. Based on some mathematical inequalities, we have obtained our results. The obtained results can apply to some fractional type difference equations as well.